2017
DOI: 10.3748/wjg.v23.i39.7087
|View full text |Cite
|
Sign up to set email alerts
|

Detection of KRAS G12D in colorectal cancer stool by droplet digital PCR

Abstract: AIMTo assess KRAS G12D mutation detection by droplet digital PCR (ddPCR) in stool-derived DNA from colorectal cancer (CRC) patients.METHODSIn this study, tumor tissue and stool samples were collected from 70 patients with stage I-IV CRC diagnosed by preoperative biopsy. KRAS mutational status was determined by pyrosequencing analysis of DNA obtained from formalin-fixed paraffin-embedded (FFPE) tumor tissues. The KRAS G12D mutation was then analyzed by ddPCR in FFPE tumors and stool-derived DNA from patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 51 publications
(62 reference statements)
0
5
0
Order By: Relevance
“…Although CEA has low sensitivity for monitoring CRC, and its benefit to overall survival remains under debate (Primrose et al, 2014), other proteins show some promise, such as epidermal growth factor-like domain 7 (EGFL7) (Hansen et al, 2017). In addition, body fluids other than blood (e.g., urine, saliva, pleural fluid, cerebrospinal fluid, and stool) show potential for monitoring tumor biomarkers (Olmedillas-Lopez et al, 2017; Siravegna et al, 2017a).…”
Section: Discussionmentioning
confidence: 99%
“…Although CEA has low sensitivity for monitoring CRC, and its benefit to overall survival remains under debate (Primrose et al, 2014), other proteins show some promise, such as epidermal growth factor-like domain 7 (EGFL7) (Hansen et al, 2017). In addition, body fluids other than blood (e.g., urine, saliva, pleural fluid, cerebrospinal fluid, and stool) show potential for monitoring tumor biomarkers (Olmedillas-Lopez et al, 2017; Siravegna et al, 2017a).…”
Section: Discussionmentioning
confidence: 99%
“…This work shows that Kras G12D was detected in OCs-1 when these cells were exposed without cell contact with CT26.WT cells in an enriched culture closer to liver microenvironment. Since the expected incorporation of Kras G12D in OC-1 cells was very low 7 , we decided to perform a ddPCR, which presents a higher sensitivity and accuracy of detection than other methods [39][40][41][42][43] . OCs-1 incorporated this oncogene in a stable way, while OCs-2 and OCs-3 were less susceptible.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to our present results, codon 12 mutations were the most common KRAS mutations found in our previous study on Iranian samples, although other KRAS mutations at codons 12, 13, 20, 63, 117, 146 and 43 were also found previously[ 13 ]. Additionally, a recent study demonstrated the detection of KRAS G12D mutation in stool samples from patients with colorectal carcinoma by using droplet PCR[ 17 ]. Clinical data available from those patients for who KRAS testing in tumor tissue was carried out correlated to KRAS mutation status in stool.…”
Section: Discussionmentioning
confidence: 99%